EfektivitasPerendaman Ekstrak Buah Bakau (Sonneratiaalba)sebagaiPenghambatPertumbuhan Bakteri terhadapMutu IkanToman - Tyas Wara Sulistyaningrum; Wahyuni Said (Daun: Jurnal Ilmiah Pertanian dan Kehutanan, 2020)
This research was conducted to study the effect of mangrove fruit (Sonneratia alba) extract submersion as a bacterial growth resistor in giant sneakhead (Channa micropeltes) fish in the process of preserving the fish.The design used in this study was with 3 treatments. Treatment A without the addition of mangrove extracts, treatment B with submersion of 2 (mangrove fruit):1(water) mangrove extracts, and treatment C with submersion of 3:1 mangrove extracts. The parameters which being observed included the Total Plate Number (ALT) test and the pH test.The results of the study showed that the lowest total bacterial colonies were found in the treatment with the 3:1 submersion of mangrove extracts, which was 8,153x103. The use of mangrove fruit extract in this study was able to extend the shelf life of fresh fish for one week, with temperatures less than 5ºC.